2013
DOI: 10.1155/2013/912310
|View full text |Cite
|
Sign up to set email alerts
|

N-n-Butyl Haloperidol Iodide Ameliorates Cardiomyocytes Hypoxia/Reoxygenation Injury by Extracellular Calcium-Dependent and -Independent Mechanisms

Abstract: N-n-butyl haloperidol iodide (F2) has been shown to antagonize myocardial ischemia/reperfusion injury by blocking calcium channels. This study explores the biological functions of ERK pathway in cardiomyocytes hypoxia/reoxygenation injury and clarifies the mechanisms by which F2 ameliorates cardiomyocytes hypoxia/reoxygenation injury through the extracellular-calcium-dependent and -independent ERK1/2-related pathways. In extracellularcalcium-containing hypoxia/reoxygenation cardiomyocytes, PKCα and ERK1/2 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous studies on cardiomyocytes revealed that ERK1/2 also mediates Egr-1-dependent H/R injury (Zhang et al, 2013). Although some studies proposed that JNK and ERK1/2 are the chief upstream signals of Egr-1-mediated lung I/R injury or pulmonary alveolar macrophage H/R injury (Fujita et al, 2004; Yamamoto et al, 2011), p38 also has been shown to contribute to H/R injury in human umbilical vein endothelial cells (Millar et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies on cardiomyocytes revealed that ERK1/2 also mediates Egr-1-dependent H/R injury (Zhang et al, 2013). Although some studies proposed that JNK and ERK1/2 are the chief upstream signals of Egr-1-mediated lung I/R injury or pulmonary alveolar macrophage H/R injury (Fujita et al, 2004; Yamamoto et al, 2011), p38 also has been shown to contribute to H/R injury in human umbilical vein endothelial cells (Millar et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Extensive studies demonstrate that MAPKs (ERK1/2, JNK, p38) are involved in I/R injury. We previously demonstrated that JNK and ERK1/2 mediate Egr-1 induction during H/R injury in H9c2 cells and primary cardiomyocytes, respectively, with ROS/Egr-1 signaling participating in the former (Zhang et al, 2013, 2015). It remains unknown whether MAPK is activated by H/R stimuli in CMECs, and whether the other two MAPK pathways, besides JNK, are involved in CMEC ROS/Egr-1 signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research studying the efficacy and mechanism of action of F 2 revealed that F 2 could improve I/R or hypoxia/reoxygenation (H/R)-induced myocardial tissue or myocardial cell damage by blocking membrane L-type Ca 2 + channels and inhibiting Egr-1 overexpression. Classic calcium antagonists also inhibit the expression of Egr-1, suggesting that the F 2 -mediated inhibition of Egr-1 expression might be related to its inhibition of Ca 2+ 10 12 13 14 . In addition, we found that F 2 could antagonize I/R- or H/R-induced decreased SOD activity and increased malondialdehyde (MDA; an oxidative stress product) level, which suggested that F 2 might play a negative regulatory role in abnormal ROS generation during myocardial I/R or H/R 15 .…”
mentioning
confidence: 99%
“…A previous study demonstrated that NF-κB is activated via MAPKs, including SAPK/JNK, p38 MAPK and eRK1/2. MaPKs are considered to be evolutionarily conserved and respond to stress by activating signal transduction during a phosphorylation cascade from cytoplasmic to nuclear targets (55,56).…”
Section: Discussionmentioning
confidence: 99%